(3CSfi GdeWGdH aj aVd Ydi Hf CHj WGdHs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj , J (B833 (3g` s
(3ChdgG (B:s
(3Chd HYO GdHSedI (B: (3GdcJGH GdNGeS , cJGH CSfi GdeWGdH ai aVd SjOfG CejQ GdeDefjf CHj GdMSf Ydi Hf CHj WGdH QVi Gddg YfgeG , hajg YTQhf HGHkG hKdGKI YTQ aUdkG GdHGH GdChd ai CSeg s
(3BNQgG (B:s
(3haGWeI JRhLgG SYjO Hf GdCShO ef Hfi MGQK , hGddg CYde GfJgi cJGH CSfi GdeWGdH HYhf Gddg hcQeg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B2s
(3cJHJ GdYfhGfGJ GdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B275 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B292 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B188s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs